Digital Literacy of Open Access Services to Support Online Learning During The Covid-19 Pandemic - Wa Ode Lusianai; Muhamad Djufri Rachim; Muliati; Astin (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
The covid-19 pandemic has changed the pattern of learning and information tracing in the world of education. This condition becomes a challenge for academics amid various limitations and new habits. In addition to the problem of online learning, currently, students are also faced with difficulties in finding and accessing references to support online learning given the limitations of library services that have not provided loans and reading services online. This condition is faced by the partner of the service program, namely students of Fisip UHO. Problems faced by partners, first limited knowledge in access ebook services and open access e-journal. Second, the ability to use Mendeley as a means of citation scientific work. Solving the problem is done through ebook access training, e-journal and the use of Mendeley continued with the practice of finding open access reference sources and doing the citation independently in Mendeley The results showed significant changes in knowledge and skills for access to ebooks and e-journal services as well as Mendeley. There are only 60% of partners understand ebook access, 64% understand e-journal access, and there are 33.3% of partners who ady understand using Mendeley. This percentage value was obtained through the distribution of questionnaires before the training activities to 22 participants. After the training was carried out there was a change of one part to 100% of partners already understunderstooding ebook and e-journal services, but only 93.8% were able to use Mendeley.